New digital adherence devices could prevent millions of strokes from atrial fibrillation by the end of the next century. (October 2017) - Boehme, Philip; Wienand, Peter; Herrmann, Maximilian; Truebel, Hubert; Mondritzki, Thomas
Abstract: The effectiveness and safety of a pharmacologic intervention is highly dependent on patient's capability to follow the recommended treatment regimen. Non-adherence to pharmacologic treatments is associated with worsening conditions including hospitalization and death. This is a significant burden to healthcare systems on a global scale with non-adherence rates being as high (or higher) as 50% in the first treatment year. The most common causes for non-adherence are forgetfulness, busy lifestyle or complexity and changes in therapeutic schedules. In conditions like atrial fibrillation (AFib) this leads to a drastic increase in event rates, e.g. strokes. Patients diagnosed with AFib are strongly recommended to receive anticoagulant treatments for stroke prevention. Treatments with Vitamin K antagonists or novel oral anticoagulants (NOACs) can dramatically lower the risk of ischemic strokes in the presence of AFib. Non-adherence can expose the patients to an increased stroke risk. This is especially true for NOACs, due to their short half-life. Patients have to take these medications once or twice daily for adequate stroke prevention, i.e., single non-use of the medication can already diminish or reset the anticoagulative effect. Adherence devices could help improve patient's compliance by reminder or feedback function. They have shown to be successful in a number of clinical trails. Especially, newer devices that make use of digital technologies show promising results but are not used broadly in clinical practice. Here we provide evidence for our hypothesis that newly available adherence devices might increase adherence rates and thereby reduce the number of strokes in patients with AFib.